Two Monoclonal Bands in Gamma Region onSerum Protein Electrophoresis; a Case Report - Younas, Muhammad; Hashim, Rizwan; Khan, Farooq Ahmad (International Journal of Pathology, 2018)
Serum protein electrophoresis (SPE) is a useful technique to separate various serum pro-teins based on their electrical charges and molecular weight. Normally gamma region is characterized by a polyclonal broad band. In Plasma cell dyscrasia we find single monoclonal prominent band. Two distinct bands in this region are quite rare. Here we present such an interesting case. .